Effects of tobacco control policy on cardiovascular morbidity and mortality in Russia. (29th October 2018) - Gambaryan, Marine; Reeves, Aaron; Deev, Alexander; Popovich, Marina; Drapkina, Oxana; Snell, Andrew; Stuckler, David; Mauer-Stender, Kristina; Mikkelsen, Bente; Boytsov, Sergey
Abstract: Background: According to the Global Adult Tobacco Survey carried out in Russia in 2009, the country had one of the highest smoking prevalence rates in Europe. In response to this health and economic burden, Russia implemented a comprehensive Tobacco Control Law (TCL) in 2013, which has been associated with a 21.5% relative decline in adult smoking prevalence in 2016 compared with 2009. This study tests the impact of the TCL on cardiovascular disease (CVD) related health outcomes, including morbidity and mortality. Method: The study evaluated the TCL as an intervention in a natural experiment during the period 2003–2015. A synthetic control was created as a comparator, using data from countries that did not have a comparable comprehensive tobacco control intervention. Changes in trends in CVD outcomes – hospital discharge rates (HDRs) and standardized death rates (SDRs) – were then compared to test for an impact associated with the TCL. Results: Pre-intervention trends in CVD-related HDRs were similar between Russia and the synthetic control, but became divergent after the TCL with greater benefit observed in Russia. This implies a beneficial impact of the TCL on CVD related morbidity in the Russian population. Whilst SDRs continued to reduce in both Russia and the control, the impact of TCL is less clear. Conclusion: This study provides further evidence to support comprehensive tobacco control in line with the WHO Framework Convention for Tobacco Control (WHO FCTC). Alongside a reduction in tobacco consumption, smoking-related CVD morbidity appears to benefit quite soon after implementation, whilst smoking-related deaths might need a longer post-intervention period to be detectable.